О разграничении грамматических фopм в языке “казанья” М. Смотрицкого - Ясюлевич, Л. В. (Kalbotyra, 1991)
In the paper an attempt is made to show the influence of the Old Church Slavonic grammar (1619) by M. Smotritsky on his notions about the orthographical norms of the “prosta mova” language (“simple Russian” in the South-West). The analysis of some orthographical rules of the sermon “Kazanie”, 1620) proves that M. Smotritsky uses the principle of the graphical forms differentiation according to his grammar.Complicated syntax of the sermon demands such differentiation for a more accurate definition of grammatical meanings for the sake of expressiveness.